MODERN TREATMENTS FOR ADJUSTMENT INDIVIDUAL LABOR DISPUTES - Грабовська, Ганна Миронівна; Подковенко, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the authors investigate modern ways of settling labor disputes. Research methods: while writing the article, methods of analysis and synthesis were used. Used comparative method of research. Results: the authors emphasize the problem of increasing the level of protection of labor rights and socio-economic interests of workers, realizing the opportunity of each citizen to uphold their rights personally. The authors agree with the opinion of scientists about the need for changes in labor legislation, the search for innovative approaches to the resolution of various labor disputes. Discussion: separately, the authors focus on the effectiveness of the implementation of conciliation procedures in labor law.